Design and Fabrication of Tapered Dielectric for Broadband and Wide Incident Angle Transmission - Yoon, Daeyeong; Na, Dong Yeop; Park, Yong Bae (IEEE Transactions on Antennas and Propagation, 2022)
We propose a novel design procedure for a 2-D array of tapered dielectric structures for broadband and wide-incident-angle transmission. We exploit a stereolithography apparatus (SLA)-type 3-D printer to fabricate tapered dielectric samples. This technology eliminates the costly and complicated processes (e.g., perforation and etching) that are required in the fabrication of tapered dielectric structures. Specifically, we adopt the rigorous coupled wave analysis (RCWA) technique to extract the effective permittivity (EP) of a tapered dielectric unit structure. An optimization algorithm is employed to determine the ultimate optimal design parameters for the maximum transmittance. The free-space measurement is performed to evaluate the electromagnetic (EM) performance of designed samples. We demonstrate that a 2-D array of optimized tapered dielectric unit structures can exhibit enhanced transmission property in comparison to a half-wavelength dielectric layer and tapered dielectric structure without optimization, viz. above 60% transmittance over the entire Ka-band up to 60° of the incidence angle for both transverse electric (TE) and magnetic polarizations.
Keywords: 2D-arrays; Broadband and wide-incident-angle transmission; Broadband Communication; Dielectric radome; Dielectric structure; Impedance; Incident angles; Ka band; Tapered dielectric; Unit structure; 3-D printer; broadband and wide-incident-angle transmission; dielectric radome; Ka-band; tapered dielectric